A novel multisite confocal system for rapid Ca2+ imaging from submicron structures in brain slices. Issue 3 (18th December 2017) - Filipis, Luiza; Ait Ouares, Karima; Moreau, Philippe; Tanese, Dimitrii; Zampini, Valeria; Latini, Andrea; Bleau, Chun; Bleau, Charlie; Graham, Jeremy; Canepari, Marco
Abstract : In brain slices, resolving fast Ca 2+ fluorescence signals from submicron structures is typically achieved using 2‐photon or confocal scanning microscopy, an approach that limits the number of scanned points. The novel multiplexing confocal system presented here overcomes this limitation. This system is based on a fast spinning disk, a multimode diode laser and a novel high‐resolution CMOS camera. The spinning disk, running at 20 000 rpm, has custom‐designed spiral pattern that maximises light collection, while rejecting out‐of‐focus fluorescence to resolve signals from small neuronal compartments. Using a 60× objective, the camera permits acquisitions of tens of thousands of pixels at resolutions of 250 nm per pixel in the kHz range with 14 bits of digital depth. The system can resolve physiological Ca 2+ transients from submicron structures at 20 to 40 μm below the slice surface, using the low‐affinity Ca 2+ indicator Oregon Green BAPTA‐5N. In particular, signals at 0.25 to 1.25 kHz were resolved in single trials, or through averages of a few recordings, from dendritic spines and small parent dendrites in cerebellar Purkinje neurons. Thanks to an unprecedented combination of temporal and spatial resolution with relatively simple implementation, it is expected that this system will be widely adopted for multisite monitoring of Ca 2+ signals. Abstract : A rapid confocal system, based on a custom‐made spinning disk and an ultrafast complementary metal oxide semiconductor (CMOS) camera, was developed for Ca 2+ imaging in brain slices. The system can resolve signals from submicron neuronal structures located at 20 to 40 μm below the slice surface. Using this approach, it is possible to record fast Ca 2+ transients from submicron structures, such as dendritic spines, from tens of thousands of sites simultaneously. Coloured scale map of the fast Ca 2+ transient associated with parallel fibre stimulation in dendrites and spines of a cerebellar Purkinje neuron.